2016
DOI: 10.1159/000444252
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatitis C Virus Infection Is Positively Associated with Gallstones in Liver Cirrhosis

Abstract: Aim: To elucidate the prevalence and risk factors of gallstone disease (GD) among patients with liver disease and explore their association with the aetiology and severity of hepatic injury. Methods: We analysed 4,832 subjects of hepatic injury induced by one of the following aetiologies: hepatitis B virus (HBV) infection, hepatitis C virus (HCV) infection, excessive alcohol consumption. The risk factors significantly associated with GD were analysed using stepwise logistic regression analysis, the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It is unknown whether HBV infection is associated with choledocholithiasis [76]. A significantly increased risk of developing gallstones among HCV-infected patients was reported [77][78][79][80][81][82][83]. HEV genotype 3 infection was also found to be associated with gallstone-related diseases, including biliary pancreatitis [84].…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether HBV infection is associated with choledocholithiasis [76]. A significantly increased risk of developing gallstones among HCV-infected patients was reported [77][78][79][80][81][82][83]. HEV genotype 3 infection was also found to be associated with gallstone-related diseases, including biliary pancreatitis [84].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not find a positive correlation between TBIL levels and gallstone formation. Correlations between TBIL levels and GD remain controversial and needed to be further discussed combined with gallstone type 7 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Determining the potential relationship between the development of gallstones and the etiology of CLD is of great interest, as previous research has suggested that HCV infection is a relevant risk factor for gallstone formation 6 . Recent studies have found that gallstones may occur more frequently in patients infected with HCV than in either patients infected with HBV or alcoholics 7 10 . In Italy, a multicenter survey demonstrated that GD prevalence among patients with liver cirrhosis was associated with HCV infection but not with excessive alcohol consumption 11 .…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] In patients with chronic liver disease, the presence of gallstones is associated with the degree of liver dysfunction, with gallstone formation occurring more readily in liver cirrhosis compared to normal biochemistry or chronic hepatitis without cirrhosis. [16] Gallstones are found in chronically infected HCV patients at a younger age than in those without liver disease and are associated with central obesity and liver steatosis, but not inherited gallstone disease. [17] Although the complex relationship between HCV infection and gallstone disease is not explained precisely, biliary lithogenesis is suggested as a related factor to HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] The male-dominant prevalence of cholelithiasis in chronic HCV-infected individuals may be attributable to age over 50 years and more progressive underlying liver pathology in males compared to females; anti-HCV was only associated with males, and not with females. [16] Nevertheless, women of all ages are still twice as likely as men to develop cholesterol gallstones from puberty through childbearing years before tapering off, highlighting the possible influence of female sex hormones. [21,22]…”
Section: Introductionmentioning
confidence: 99%